Inhabiting the bedroom. Daily life and mobility of the middle classes residing in expansion areas of the cities of La Plata and Mar del Plata, during confinement due to Covid-19 (Huellas, 2024)
In this article, we start from the diagnosis that during the 2020 pandemic, in most States a techno-expert management of the crisis prevailed. This tendency underestimated the differential conditioning factors that shaped and still shape the daily life of different populations and territories. On this basis, we will analyze how territorial inscriptions, the place occupied in the social structure and daily mobility prior to the pandemic, shaped the way in which COVID-19 was experienced. In particular, we will analyze how the middle classes residing in the expansion areas of La Plata and Mar del Plata faced COVID-19; how their previous daily mobilities were put into play in this process and how this impacted their daily life during the confinement.  The article is based on the fieldwork carried out in the framework of the project “Flujos, fronteras y focos. La imaginación geográfica en seis periferias urbanas de la Argentina durante la pandemia y la pos pandemia del COVID19”. More specifically, we focused our analysis on 21 in-depth interviews with middle-class residents of the expansion areas from both cities.